Thrombocytopenia in Children - Jan, Muhammad Ali (Journal of Postgraduate Medical Institute, 2011)
To find out the etiology, clinical profile and complications of thrombocytopenia in children. This study was conducted at HSTH Peshawar from June 1995 to December 1996. Paitents upto 12 years of age, presenting with mucocutaneous bleeding or thrombocytpenia on peripheral smear were included in the study. Detailed history and physical examiantion was followed by relevant investigations. Patients with complications and platelet count < 30 x 10/L were given steroids. Acute ITP is the leading cause of thrombocytopenia in children. use of steroid should be recommended in proper dosage where indicated.